Strategic management, management control practices and public value creation: the strategic triangle in the Swedish public sector - Höglund, Linda; Mårtensson, Maria; Thomson, Kerstin (Accounting auditing and accountability journal, 2021)
PurposeThe purpose of this paper is to enhance understanding of the conceptualisation and operationalisation of public value in practice by applying Moore's (1995) strategic triangle as an analytical framework to study strategic management and management control practices in relation to public value.Design/methodology/approachThe paper uses an interpretative longitudinal case study approach including qualitative methods of document studies and interviews between 2017 and 2019.FindingsIn the strategic triangle, the three nodes of authorising environment, public value creation and operational capacity are interdependent, and alignment is a necessity for a strategy to be successful. But this alignment is vulnerable. The findings suggest three propositions: (1) strategic alignment is vulnerable to management control practices having a strong focus on performance measurements, (2) strategic alignment is vulnerable to standardised management control practices and (3) strategic alignment is vulnerable to politically driven management control practices.Originality/valueWith the strategic triangle as a base, this paper tries to understand what kind of management control practices enable and/or constrain public value, as there has been a call for this kind of research. In this way it adds to earlier research on public value, to the growing interest in the strategic triangle as an analytical framework in analysing empirical material and to the request for more empirical studies on the subject. The strategic triangle also embraces political factors, government agendas and political leadership for which there has also been a call for more research.